TEACHERS’ PERCEPTION ON ICT-BASED ENGLISH TEACHING - Yayan Suryana (English Review: Journal of English Education, 2013)
Abstract: This article was related to the teachers’ perception on the application of ICT-based English teaching in Senior High School and the readiness of the teachers and schools in applying the 2013 Curriculum. This qualitative data was described from the interview and the survey during the socialization of the 2013 Curriculum. 8 participants of different ages from different Senior High School in Kuningan Regency were interviewed by phone, direct interview, and Facebook-chatting. The findings showed that most of the senior teachers (80%) of more than 50 years of age were not motivated in using the ICT, 20% of them were familiar with ICT; 60% of the teachers between their 30s and 40s generally understood how to use ICT but seldom implemented the ICT based English teaching because of lack of ICT facilities. Almost 95 % of new English teachers were familiar with ICT and they applied the ICT-based English teaching when the ICT facility was available. Their reasons of not using ICT were lack of ICT literacy, taking too long to learn, and the fact that it was expensive and not always available. The conclusion of this research was that the application of the ICT-based English teaching could not be applied 100% because some teachers were still illiterate with ICT and the ICT facilities were still limited. Keywords :ICT,Teachers’ Perception, the 2013 Curriculum, ICT literacy, ICT-based English Teaching